ANALISIS PERUBAHAN DIMENSI CAMSHAFT DAN TINGGI BUKAAN KATUP TERHADAP KINERJA MESIN BAKAR 115 CC - Yudha Antariksa Diyat Saputra (2022)
Motorcycles are vehicles that are widely used today. Motorcycles use combustion engines to operate and produce residual gases from combustion, including Carbon Monoxide (CO), Carbon Dioxide (CO2), Hydrocarbon (HC), and Oxygen (O2). To reduce the production of these pollutants, a study was conducted to optimize the performance of the 4 stroke combustion engine used by motorcycles by modifying the camshaft, namely making the lift vary on the camshaft used. The goal is to produce the most effective valve opening height, both in terms of fuel consumption, emissions, and power generated.